Research in Personnel and Human Resources Management - Buckley, M. Ronald (Emerald Publishing Limited, 2024)
This volume offers several original scholarly contributions written by thought leaders in the field of human resources management
Description based on publisher supplied metadata and other sources
Keywords: Personnel management; Supervision of employees